Association of Serum Sex-Hormone-Binding Globulin in Pregnant Women with Gestational Diabetes Mellitus - Sharmin, Asma; Khan, Mohammad Reza Hossain; Jahan, Jesmin; Md Shameem, -; Afruza, Shahzadi; Keya, Summi Leunard (TAJ: Journal of Teachers Association, 2021)
Background & objective: Gestational diabetes mellitus (GDM) is a common pregnancy complication and is associated with increase maternal and neonatal morbidity. Circulating Sex hormone-binding globulin (SHBG) levels are inversely associated with insulin resistance, and insulin resistance is the hallmark of GDM. This study was carried out to investigate SHBG level in pregnancy and to analyze the association of SHBG with GDM. Materials & Methods: This case-control study was carried out in the antenatal clinic of the department of obstetrics & gynecology, BSMMU, Shahbag, Dhaka, over a period of 12 months between August 2017 to July 2018. Participants were 80 in number, aged between 18 to 35 years, having singleton pregnancy with 24 to 28 weeks of gestation. 40 GDM cases were enrolled as the case, and 40 non-GDM cases were enrolled as the control. Pregnant women with overt diabetes/diabetes in pregnancy, previous history of GDM, pre-eclampsia, gestational/chronic hypertension, known case of liver disease, thyroid disorder, acute or chronic renal disease, congenital fetal anomaly, multiple pregnancies, smoking, H/O polycystic ovary syndrome (PCOS) was excluded from the study. Comparison of means made by using Student t-test and categorical data were analyzed by Chi-square Test, and Pearson's correlation was utilized between serum sex-hormone binding globulin level nmol/L with fasting plasma glucose (mmol/L) and 2-hour after 75g glucose (mmol/L). Statistical significance was set at p < 0.05. Results: The median value of serum SHBG was 245.0nmol/L (195.8-278.1) in the case group and 390.1nmol/L (310.2-465.3) in the control group. Women with GDM were found to have significantly lower levels of SHBG compared to the controls (p<0.05). There was a moderate negative significant correlation (r=-0.621; p=0.001) between fasting plasma glucose (mmol) with serum SHBG (nmol/l) in GDM patients. On the other hand, there was a weak negative but not significant correlation (r=-0.229; p=0.155) was found between 2 hours after plasma glucose with serum SHBG in the GDM group. Conclusion: A significantly lower SHBG level is associated with GDM. TAJ 2021; 34: No-1: 80-85